An investigation of the private speech phenomenon in the collaborative interaction of Iranian adult EFL learners - Abadikhah, Shirin; Khorshidi, Afsaneh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The purpose of this study was to investigate the use of private speech in collaborative interactions of Iranian adult EFL learners. More specifically, it examined (a) if adult EFL learners used private speech during task completion, (b) whether they externalised their private speech in Persian (L1) or English (L2), and (c) if there is any relationship between the amount of private speech and successful task completion. Twelve female EFL learners from two proficiency levels - advanced (3 pairs) and beginner (3 pairs) - took part in this study. The learners’ conversations were audio and video-recorded during the completion of a picture description task. The peer-peer interaction was transcribed and analysed for the occurrence of private speech. The results indicated that both groups employed private speech during task completion; however, the advanced learners externalised it predominantly in English. Although no relationship was found between the amount of private speech and successful task completion, the use of private speech helped them get control over the task.